Antibodies targeting G protein-coupled receptors: Recent advances and therapeutic challenges. Issue 5 (4th July 2017) - Ayoub, Mohammed Akli; Crépieux, Pascale; Koglin, Markus; Parmentier, Marc; Pin, Jean-Philippe; Poupon, Anne; Reiter, Eric; Smit, Martine; Steyaert, Jan; Watier, Hervé; Wilkinson, Trevor
ABSTRACT: Le STUDIUM conference was held November 24–25, 2016 in Tours, France as a satellite workshop of the 5 th meeting of the French GDR 3545 on "G Protein-Coupled Receptors (GPCRs) -From Physiology to Drugs, " which was held in Tours during November 22–24, 2016. The conference gathered speakers from academia and industry considered to be world leaders in the molecular pharmacology and signaling of GPCRs, with a particular interest in the development of therapeutic GPCR antibodies (Abs). The main topics were new advances and challenges in the development of antibodies targeting GPCRs and their potential applications to the study of the structure and function of GPCRs, as well as their implication in physiology and pathophysiology. The conference included 2 sessions, with the first dedicated to the recent advances in methodological strategies used for GPCR immunization using thermo-stabilized and purified GPCRs, and the development of various formats of Abs such as monoclonal IgG, single-chain variable fragments and nanobodies (Nbs) by in vitro and in silico approaches. The second session focused on GPCR Nbs as a "hot" field of research on GPCRs. This session started with discussion of the pioneering Nbs developed against GPCRs and their application to structural studies, then transitioned to talks on original ex vivo and in vivo studies on GPCR-selective Nbs showing promising therapeutic applications of Nbs in important physiologic systems, such as the central nervous and the immune systems, as well as in cancer. The conference ended with the consensus that Abs and especially Nbs are opening a new era of research on GPCR structure, pharmacology and pathophysiology.